Erratum: PARP1 promotes gene expression at the post-transcriptional level by modulating the RNA-binding protein HuR - Yueshuang Ke (Nature Portfolio, 2017)
Nature Communications 8 Article number:14632 (2017); Published: 8 March 2017; Updated: 31 March 2017 The original version of this Article contained an error in the spelling of post-transcriptional in the title of the paper. This has now been corrected in both the PDF and HTML versions of the Article.